Renal involvement in the Laurence-Moon-Biedl syndrome: report of a case and a sibling - Cengiz, Kuddusi; Tanyeri, Fulya; Aykın, Aykut C. (The Turkish Journal of Pediatrics, 1988)
A twenty-seven-year-old male who was hospitalized because of renal disease and his thirteen-year-old sister, both having the Laurence-Moon-Biedl syndrome, are presented and the related literature is reviewed for the presence of renal disorders in regard to this syndrome.